Analysis of Volleyball Extracurricular Physical Fitness at SMA Negeri 7 Bengkulu Selatan - Feby Heder Hedri; Feby Elra Perdima; Martiani Martiani (Sinar Sport Journal, 2021)
This study aims to determine the level of physical fitness of male students in volleyball extracurricular at SMA Negeri 7 Bengkulu Selatan. This research method uses descriptive qualitative research methods. This type of research is in the form of descriptive to provide understanding and interpret the data as it is. The population in this study were male students who took part in volleyball extracurricular at SMA Negeri 7 Bengkulu Selatan as many as 20 people and the research sample used total sampling, namely the sampling technique by taking all members of the population as respondents or a sample of 20 people. The results of the calculation of the data, obtained the average physical fitness of male students in volleyball extracurricular at SMA Negeri 7 Bengkulu Selatan from 20 people with a value of 17.5 points and included in the medium category. Based on the results of research and data calculations that have been carried out, it can be concluded that the level of physical fitness of male students in volleyball extracurricular at SMA Negeri 7 Bengkulu Selatan is in the medium category.